Trust-Based Cooperative Spectrum Sensing Algorithm in Power Dedicated Network - Jinping Cao; Wei Li; Yiying Zhang (Dianxin kexue)
To fulfill the communication needs of smart distribution and utilization system,a novel power dedicated network has been developed.The system faces a problem that it may operate coexisted with a 230 data transceiver system.In order to keep the two systems operating stably and efficiently at the same time,a trust-based cooperative spectrum sensing algorithm was presented.According to the characteristics of user behavior,cognitive radio users were classified into fiduciary users,lapsed users and malicious users.By analyzing the relationship among detection result,credibility of cognitive radio users and communication channel signal-to-noise ratio,the credibility weight of cognitive radio users was given,and a trust-based cooperative spectrum sensing algorithm was proposed.The simulation results show that the algorithm improves detection performance effectively.